Anxiety levels and their relationship to learning styles for some swimming skills among students of the Faculty of Physical Education and Sports Sciences at Al-Zawiya University (Al-Farooq Journal of Sciences, 2026)
The present study aimed to identify the level of anxiety and its relationship to learning styles in acquiring selected basic swimming skills (floating, gliding, flutter kicks, and front crawl) among first-year students at the Faculty of Physical Education and Sports Sciences, University of Zawia. The descriptive-correlational method was adopted. The research population comprised (55) first-year students enrolled in the swimming course for the academic year 2025/2026. The final sample consisted of (30) students selected randomly, excluding pilot study participants and those with prior swimming experience. Data collection instruments included a Swimming Learning Anxiety Scale, the VARK Learning Styles Inventory, and a Technical Skill Assessment Rubric. Statistical analyses involved mean scores, standard deviations, Pearson correlation coefficients, and one-way ANOVA. Findings revealed moderate to high swimming anxiety levels, with the kinesthetic style predominating, followed by the visual style. Furthermore, a statistically significant inverse correlation was found between anxiety levels and skill acquisition. Significant differences were observed in anxiety levels across learning styles, favoring the kinesthetic approach. The study recommends implementing psychological preparation strategies to minimize aquatic anxiety and tailoring swimming pedagogies to individual learning preferences.
Keywords: Anxiety, Learning Styles, Swimming Skills, Faculty of Physical Education and Sports Sciences